Fiscal impoverishment in rich democracies - Manuel Schechtl; Rourke L. O'Brien (Luxembourg Income Study (LIS), 2022)
This article introduces fiscal impoverishment as a novel framework for comparative poverty research. We invert standard analyses of welfare state policy and household poverty by focusing not on poverty alleviation but poverty creation and exacerbation. Using harmonized household survey data, we show how the income and payroll taxes most rich countries rely on to finance the public sector serve to push households (further) into poverty. We estimate that across rich democracies on average about 1 in 4 households in poverty are made poorer on net after taxes and transfers; with fiscal impoverishment levels ranging from less than 10% in some countries to more than 70% in others, revealing extreme cross-national variation in how the pocketbooks of poor households are impacted by national tax and transfer policy. We show that fiscal impoverishment is relatively more common in continental and southern European welfare states and relatively less common in Anglo-liberal and Nordic countries but for different reasons. Counterfactual simulations show that reducing income tax liability would increase disposable income and substantially reduce household poverty in many welfare states. We consider the implications of fiscal impoverishment for assessing welfare state performance and for comparative poverty research.
Keywords: 330; Haushaltseinkommen; Armut; Einkommensverteilung; Einkommensteuer; Sozialversicherungsbeitrag; Sozialstaat; Welt